Optical Coherence Tomography Angiography Evolution of Choroidal Neovascular Membrane in Choroidal Rupture Managed by Intravitreal Bevacizumab - Massimo Lorusso; Luisa Micelli Ferrari; Eleni Nikolopoulou; Tommaso Micelli Ferrari (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of a 25-year-old man with choroidal neovascularization (CNV) secondary to traumatic choroidal rupture treated with intravitreal bevacizumab and to evaluate the vascular structure of the area near the traumatic choroidal rupture. Methods. The patient underwent complete ophthalmologic evaluation, including best-corrected visual acuity (BCVA), intraocular pressure, anterior segment and funds examination, and optical coherence tomography angiography (OCTA) at baseline and on each follow-up visit. Fluorescein angiography (FA) was performed at baseline. Intravitreal bevacizumab was administered at the time of choroidal neovascular membrane diagnosis. Results. At baseline, ophthalmoscopic examination of the left eye revealed four subretinal macular hemorrhages and two choroidal ruptures located temporally to the fovea. On OCT angiograms, the choroidal rupture appeared as a hypointense break in choriocapillaris plexus. At 4-week follow-up, the OCTA disclosed a well circumscribed lesion characterized by numerous and fine anastomotic vessels. Patient received intravitreal injection of bevacizumab. At 6-week post injection, OCTA documented regression of the neovascular complex. Conclusion. Choroidal neovascularization is a common complication associated with traumatic choroidal rupture and OCTA may represent a complementary diagnostic technique to evaluate the vascular structure of the area near the traumatic choroidal rupture.